LANGUAGE AND GENDER: A CASE STUDY - Wim Banu Ukhrowi; Binti Qani’ah (Journal of Research in Foreign Language Teaching (JRFLT), 2022)
Many factors influence the acquisition of a language. One of the factors influences gender differences. The language used by men and women is sometimes different in terms of time used, words produced, and standard language used. Based on findings from related areas, this research aims to give a comprehensive account of gender differences in second language acquisition in the Access class organized by IIEF (Indonesian International Education Foundation) collaborated with RELO (Regional English Language Officer) under the supervision of the US Embassy. There are differences in talking time used by women and men. women also uttered more words rather than men. But there is not a big difference between women and men in using the standard form of language. The data that was obtained from four men and four women participants showed that women spent more time to respond the questions. Women tend to comment on the statements in detail. The number of words uttered by women and men is different. Men produced the words on average 80 words in unlimited time which was prepared by the researcher. Women uttered more words than men. The average number of words uttered by women is 174 words. Women and men have no differences in using standard forms of the language.